Fashion trends research of Santa Catarina’s industry: analysis of the concepts of colonialism and eurocentrism (DAPesquisa, 2021)
This article focuses on the fashion trends’ researches made in the industry of Santa Catarina, relating to concepts of colonialism and Eurocentrism. Through a questionnaire applied to fashion designers, it was observed that they have Europe as their main research reference, but that they also value the analysis and forecasting of national trends. To understand this phenomenon, the literature review has a historical overview of the emergence of fashion trends and the centralization of fashion in Europe. In addition, the concepts of colonialism and Eurocentrism, disseminated in Latin America by authors such as Aníbal Quijano (2005) and Edgardo Lander (2005), are studied. The article seeks to point out the possible consequences of the hegemony of European fashion in the trend research carried out by the Santa Catarina industry, as there is a risk of losing autonomy and identity, making innovation and business value issue deficient.
Keywords: Fashion; Marketing research; Clothing and dress - Industry - Santa Catarina; Social Movement